2013
DOI: 10.21608/zumj.2013.4292
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Burden Among Caregivers of Patients With Schizophrenia in Egypt

Abstract: Most studies of family burden have been conducted in developed countries, thus it is important to conduct studies in developing countries, namely Egypt. Aim of the study: To evaluate the psychosocial burden among caregivers of schizophrenic patients. Subjects and Methods: A total of 120 schizophrenic patients attending the outpatient Clinic of Zagazig University Hospital with their primary caregivers, using Caregiver Strain Index (CSI), Caregiver Self Assessment Questionnaire (CSAQ), Hamilton Anxiety Scale, Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…They also tend to be more emotionally attached to the patients as well as the cultural norms in Eastern society that put the responsibility of caregiving in general over the women shoulders. This is the same as a study conducted in Zagazig-Egypt found that 62% of the caregivers were females (Fouad et al, 2013). It is also consistent with many previous studies, for example, in the United Kingdom, about 58% of the caregivers were women (Nolan, 2001), and other Asian studies have reported that about 70% of family caregivers were female (Chan et al, 2009), study in Nigeria where is 60% of family caregivers were females (Adeosun, 2013) as well as a recent study in Turkey 64% of caregivers were women (Yazici et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…They also tend to be more emotionally attached to the patients as well as the cultural norms in Eastern society that put the responsibility of caregiving in general over the women shoulders. This is the same as a study conducted in Zagazig-Egypt found that 62% of the caregivers were females (Fouad et al, 2013). It is also consistent with many previous studies, for example, in the United Kingdom, about 58% of the caregivers were women (Nolan, 2001), and other Asian studies have reported that about 70% of family caregivers were female (Chan et al, 2009), study in Nigeria where is 60% of family caregivers were females (Adeosun, 2013) as well as a recent study in Turkey 64% of caregivers were women (Yazici et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…In support of the present study results, a study in Africa by Foad with the aim to determine developmental and emotional differences among children in orphanage, conducted on 294 boys and girls with no parents or single parents, showed 21% depression, 45% anxiety, 61% developmental problems, and 23% self-esteem in these children, which are in line with the present study results. In his study, Fouad used Rosenberg questionnaire to assess self-esteem, which comprises 10 items on family and education, while, in the present study, modified CSEI was used for orphan children, which consists of 58 items with 4 subscales of family, academic, peers, and self [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurturing and development of these indicators begin at home and especially with parents [ 1 ]. Self-esteem is based on kindness and love of children, like a strong foundation for the house [ 2 , 3 ]. Low self-esteem causes behavioral and emotional disorders and may lead to antisocial behaviors [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%